Regulation of extracellular slime production by Actinomyces viscosus. - Ooshima, T (1981)
Extracellular slime polysaccharides produced two Actinomyces viscosus strains, T14V and T14AV, were compared. In various media containing glucose, T14Av produced abundant extracellular viscous slime polysaccharide, whereas T14V produced lower levels. Furthermore, fractionation of these polysaccharides showed that the two extracellular polysaccharides differed in molecular size and net charge. Since there was a significant difference in the relative abilities of chemically defined medium and chemically defined tissue culture medium to support slime production by T14Av, the nutritional factors influencing the production of extracellular slime were examined. Sodium bicarbonate was demonstrated to stimulate both cellular growth and the production of extracellular slime. In chemically defined medium with and without sodium bicarbonate, strain T14Av produced large quantities of viscous slime in glucose and sucrose media. In contrast, relatively low levels of slime were produced in fructose, lactose, raffinose, and inositol media, even though sodium bicarbonate stimulated the growth of T14Av in these latter media.